A social accounting matrix for Iraq - Dario Debowicz (Journal of Economic Structures, 2016)
This paper deals with the challenges associated with the generation of a social accounting matrix (SAM) in conditions where up-to-date measured data are particularly scarce and provides future researchers of economic systems with the first SAM for Iraq. It delivers a unique and updated countrywide database for use in modeling and policy analysis and applies this database to the empirical investigation into the expected effects of economic diversification in Iraq as stated in the recent Iraq National Development Plan 2013-2017.
Keywords: 330; Social accounting matrix (SAM); Semi-input-output analysis; Iraq; Economic system